Long-run relationship between sectoral productivity and energy consumption in Malaysia: An aggregated and disaggregated viewpoint - Rahman, Md Saifur; Ha, Junsheng; Shahari, Farihana; Aslam, Mohamed; Masud, Muhammad Mehedi; Banna, Hasanul; Ma, Liya (Elsevier B.V., 2015)
This paper investigates the causal relationship between energy consumption and economic productivity in Malaysia at both aggregated and disaggregated levels. The investigation utilises total and sectoral (industrial and manufacturing) productivity growth during the 1971–2012 period using the modified Granger causality test proposed by Toda and Yamamoto [1] within a multivariate framework. The economy of Malaysia was found to be energy dependent at aggregated and disaggregated levels of national and sectoral economic growth. However, at disaggregate level, inefficient energy use is particularly identified with electricity and coal consumption patterns and their Granger caused negative effects upon Gross Domestic Product (GDP) and manufacturing growth. These findings suggest that policies should focus more on improving energy efficiency and energy saving. Furthermore, since emissions are found to have a close relationship to economic output at national and sectoral levels green technologies are of a highest necessity.